The effect of added Cinnamon on the quality of biko - Zafra, Mary Anne Joy V.
ABSTRACT This study aimed to determine the effect of added cinnamon powder on the physicochemical, microbiological and sensory properties of biko upon storage at room temperature. Four biko samples were prepared including a control (biko) and biko added with 1%, 2% and 3% cinnamon powder. Results showed that cinnamon powder significantly decreased the pH level of biko from 6.22 to 5.98. The decrease in pH was probably due to the oxidation of trans-cinnamaldehyde to cinnamic acid. The water activity of the experimental and control (biko) samples on the other hand significantly decreased upon storage probably due to retrogradation and syneresis. It was visually observed that the samples became very moist and oily after three days of storage. In terms of firmness, no significant change in firmness was observed across all samples. The samples of biko with different concentrations of cinnamon had lower aerobic plate counts compared to the control (biko) during day 1 and 3 of storage perhaps due to the antimicrobial property of cinnamon. Consumer acceptance test showed that panelists seemed not to prefer biko with a very dark brown color as exemplified by biko with 3% cinnamon powder. But in terms of aroma and flavor, biko with or without cinnamon was found to be acceptable. Consumer ratings for texture significantly decreased after three days of storage across all samples. The addition of cinnamon powder in biko did not prolong the shelf life of the product. Significant processing issues such as packaging should be taken into consideration since mold growth was very evident during storage.